The Effect of Financial Ratios and Company Size on Company Financial Performance - Dwi Egalita Novia Maharani; Agustin Ekadjaja (Graduate Program of Universitas Tarumanagara, 2023)
The goal of this study is to learn more about the effect of Total Asset Turnover, Current Ratio, Leverage, and Company Size on Company Financial Performance. This study uses a sample of 26 manufacturing companies in the consumer goods industry during 2017-2020 which can be seen on the IDX obtained using the purposive sampling method. The application used for data processing in this research is E-views 12. This test results that Total Asset Turnover and Company Size have a significant impact on the Financial Results of the Firm, Current Ratio has a negative and insignificant effect on the Firm Performance, and Leverage has a negative significant impact on the Firm Performance. From this research, high-quality management is needed to encourage companies to improve their performance to figure out how to compete with the best strategies and subsequently maintain the Company’s Financial Performance for the survival of the firm.